Data Disclosure Global Developments and Perspectives - Hennemann, Moritz; von Lewinski, Kai; Wawra, Daniela; Widjaja, Thomas (Global and Comparative Data Law, 2023)
This volume presents the proceedings of the bidt "Vectors of Data Disclosure" conference held in Munich 2022. The contributions give interdisciplinary and comparative insights into various factors of data disclosure decisions - combining perspectives of law, cultural studies, and business information systems. The volume also condenses results of the corresponding bidt research project on "Vectors of Data Disclosure".